(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This study was intended to research the partial replacement of coarse aggregate with shredded rubber. The rubber used in the study was kept in three conditions. The shredded rubber was either untreated, treated with NAOH and treated with cement paste before being used in concrete. M20 mix of concrete was used in this study. The compressive strength, flexural strength and split tensile strength of concrete after 28 days of curing for replacement of rubber in the percentages of 5%,10% and 15% was done. The results show that there is a decrease in workability as the percentage of rubber is increased for all of the conditions of the shredded rubber treatment. The compressive strength test result show that there is a decrease in strength as the percentage of rubber is increased. However, when treated rubber is introduced the value of compressive strength improves. The flexural strength test results show that the maximum value of flexural strength is obtained at 5% replacement of rubber for treatment with NAOH. The results indicate that treated rubber specimens have more flexural strength when compared with the values of untreated rubber specimens. The split tensile strength shows that the value of split tensile is maximum for 15% replacement of rubber and for treatment with NAOH. The value of split tensile decreases as the percentage of rubber is increased however an improvement is seen as treated rubber is used to replace coarse aggregate.